Genomic Characteristics Distinguish Geographically Distributed Dehalococcoidia - Yang, Yi; Zhang, Yaozhi; Cápiro, Natalie L.; Yan, Jun (Frontiers in Microbiology, 2020)
Dehalococcoidia (Dia) class microorganisms are frequently found in various pristine and contaminated environments. Metagenome-assembled genomes (MAGs) and single-cell amplified genomes (SAGs) studies have substantially improved the understanding of Dia’s microbial ecology and evolution; however, update of a thorough investigation on the genomic and evolutionary characteristics of Dia microorganisms distributed in geographically distinct environments has not been implemented. In this study, we analyzed available genomic data to unravel Dia evolutionary and metabolic traits. Based on the phylogeny of 16S rRNA genes retrieved from sixty-seven genomes, Dia microorganisms can be categorized into three groups, the terrestrial cluster that contains all Dehalococcoides and Dehalogenimonas strains, the marine cluster I, and the marine cluster II. A higher ratio of horizontally transferred genetic materials was found in the Dia marine clusters compared to that of the Dia terrestrial cluster. Pangenome analysis further suggests that Dia microorganisms have evolved cluster-specific enzymes (e.g., dehalogenase in terrestrial Dia, sulfite reductase in marine Dia) and biosynthesis capabilities (e.g., siroheme biosynthesis in marine Dia). Marine Dia microorganisms are likely adapted to versatile metabolisms for energy conservation besides organohalide respiration. The genomic differences between marine and terrestrial Dia may suggest distinct functions and roles in element cycling (e.g., carbon, sulfur, chlorine), which require interdisciplinary approaches to unravel the physiology and evolution of Dia in various environments.